Biomechanical evaluation of percutaneous cement discoplasty combined with percutaneous vertebroplasty: a finite element analysis - Zhou, Xu; Qin, Shenghua; Huang, Chunhai; Li, Feiwen; Liu, Jin; Wu, Ti; Zhang, Mingzheng (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSince the introduction of percutaneous cement discoplasty (PCD), numerous studies have confirmed its clinical efficacy in elderly patients. However, PCD is also associated with risks such as bone cement leakage and vertebral fractures. The purpose of this study was to present a biomechanical evaluation of two modified versions of PCD performed in combination with percutaneous vertebroplasty (PVP).MethodsData from a CT scan of a healthy male’s lumbosacral region were used to establish finite element (FE) models of nonsurgical treatment, PCD, L4/5PCD + L4L5PVP (modified technique 1, where the bone cement in the L4/5 disc space does not connect with the L4 and L5 vertebrae) and PCIF (modified technique 2, where the bone cement in the L4/5 disc space connects with the L4 and L5 vertebrae). A compressive of preload 150 N and a moment of 10 N·m were applied to recreate flexion, extension, lateral bending, and axial rotation. The range of motion (ROM) of L3/4 and L4/5, maximum stress on the L3 inferior endplate, L4 inferior endplate and L5 superior endplate, stress on the annulus fibrosus of L4/5, and displacement of the bone cement were evaluated.ResultsBoth modified techniques outperformed the simple PCD technique in reducing stress on the endplate, stress on the annulus fibrosus, and displacement of the bone cement. The L4/5PCD + L4L5PVP technique was more advantageous in terms of reducing the incidence of postoperative complications. The addition of the PVP technique significantly enhanced spinal stability by increasing support to adjacent vertebrae, thereby reducing the risk of postoperative endplate fractures and bone cement leakage.ConclusionModified PCD combined with PVP may be a safer and more effective option for treating degenerative disc diseases, providing important references for clinical treatment.